1998
DOI: 10.1557/proc-550-215
|View full text |Cite
|
Sign up to set email alerts
|

Application of Conductive Polymers in Bone Regeneration

Abstract: The role of electromagnetism in the physiology of the human body and in the healing process is well accepted. Electroactive polymers, such as electrically conducting polymers, by virtue of their susceptibility to either electrical, mechanical, optical or thermal phenomena, could be utilized as an interface between the external world and the physiological environment1. In this study we have evaluated the utility of polypyrrole (PPy)-a conductive polymer, as an interactive substrate for inducing differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 8 publications
2
31
0
Order By: Relevance
“…With a PPy film as substrate and a working electrode, and Au and Ag wires as reference and counter electrodes respectively, a constant EF of 20 V/m ES for 1 hour induced a statistically significant increase in the osteogenic differentiation of BMSC on the thin PPy film substrates. Compared to a conductive indium tin oxide (ITO) glass control, the authors (Shastri et al, 1999) claimed that the increased osteogenic differentiation of BMSC on PPy was attributed to the chemistry of the underlying PPy substrate rather than the electrochemical byproducts formed in solution by the ES. The conducting polymer films may be used to manipulate physiologically relevant ionic interactions with living cells.…”
Section: Conducting Polymersmentioning
confidence: 99%
“…With a PPy film as substrate and a working electrode, and Au and Ag wires as reference and counter electrodes respectively, a constant EF of 20 V/m ES for 1 hour induced a statistically significant increase in the osteogenic differentiation of BMSC on the thin PPy film substrates. Compared to a conductive indium tin oxide (ITO) glass control, the authors (Shastri et al, 1999) claimed that the increased osteogenic differentiation of BMSC on PPy was attributed to the chemistry of the underlying PPy substrate rather than the electrochemical byproducts formed in solution by the ES. The conducting polymer films may be used to manipulate physiologically relevant ionic interactions with living cells.…”
Section: Conducting Polymersmentioning
confidence: 99%
“…[9] Likewise, electrical stimulation of peripheral nerve gaps in vivo improves the rate of recovery; thus, polypyrrole-based materials with biomimetic topographies have promise as nerve tissue scaffolds. [10] The concept of using CP-based materials as bone tissue scaffolds was first reported by Langer and coworkers, [11] who found that applying a potential step of 20 mV 脕 mm 脌1 across two-dimensional polypyrrole films enhanced the differentiation of bone marrow-derived stromal cells toward osteogenic outcomes, as confirmed by an increase in alkaline phosphatase (ALP) activity per cell relative to non-stimulated control substrates, [11] and further developed by others. [12] Oligoaniline-based CPs are increasingly popular biomaterials, [6i,j] and such polymers have been shown to promote osteogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Other studies have shown that cell proliferation in vitro can be regulated by electrical stimulation [27] and that bone cells are influenced when CPs are used as substrates. [21,28,29] The immature mouse osteoblast-like MC3T3-E1 cell line is traditionally used to study events such as attachment, proliferation, matrix synthesis, and matrix calcification that occur upon interaction with a material surface. [30] MC3T3-E1 cells are anchorage-dependent and thus adhesion is a critical prerequisite for subsequent cell functions such as proliferation and protein expression.…”
Section: Introductionmentioning
confidence: 99%